The neotropical species of Mesocyclops (Copepoda, Cyclopoida): An upgraded identification key and comments on selected taxa - Gutiérrez-Aguirre, Martha Angélica; Suarez-Morales, Eduardo; Cervantes-Martínez, Adrián; Elias-Gutierrez, Manuel; Previattelli, Daniel (Journal of Natural History, 2006)
In this work we present an analysis of upgraded characters used in the taxonomy of cyclopine copepods to provide a new key for the identification of the members of the freshwater genus Mesocyclops recorded in the neotropical region. This analysis, which included revision of type and museum specimens, resulted also in the clarification of the taxonomical status of two nominal species not previously revised, M. varius Dussart, 1987 and M. venezolanus Dussart, 1987. These two species are recognized herein as junior synonyms of M. brasilianus Kiefer, 1933. Considering the addition of new records (introduced Afro-Asian or Asian forms), the designation of M. araucanus Campos et al., 1974 to species rank, and the conflict of determining the taxonomical status of M. annulatus diversus , the number of taxa recognized in the region includes 20 species and one variety. A general morphological analysis of the Old and New World species allowed us to contrast and evaluate some of the differential characters of these two groups. We propose several characters that can be considered as potentially valuable to separate reliably both female and male specimens of the neotropical species. The distribution of selected species or species groups of Mesocyclops is also revised in light of this new frame. © 2006 Taylor & Francis.
Keywords: Crustacean; Invertebrate; Taxonomy; Copepoda; Cyclopoida; Mesocyclops; Mesocyclops Annulatus; Mesocyclops Brasilianus; Mesocyclops Varius; Mesocyclops Venezolanus